Adoption of Public Service Mall in Kebumen Regency - Haryani, Tiyas Nur; Nugroho, Rino A.; Nurhalima, Isnaeni (KnE Social Sciences, 2022)
The government improves the quality of public services by creating innovations. Through KEMENPANRB, the government created the Public Service Mall (MPP) innovation. Kebumen Regency is one of the areas that has the MPP. This study aimed to describe the MPP’s innovation in Kebumen by using Rogers’ innovation attributes. This study used descriptive qualitative methods. Data were collected through interviews, observation, and documentation. The validity of the data was evaluated through triangulation of sources. The results showed that the MPP innovation in Kebumen fulfilled 5 of Rogers’ innovation attributes: 1) relative advantage, the innovation reduced the costs incurred by the community in obtaining services and made services more effective and efficient; 2) compatibility, the MPP followed previous innovations, aligned with the needs of the community, and did not conflict with existing values and norms; 3) complexity, the MPP was associated with a lack of certified human resources, public understanding of IT and socialization about the MPP, but this did not hinder the running of the MPP services; 4) triability, the service was opened a few days before being inaugurated; and 5) observability, the MPP showed a positive impact where the community became more enthusiastic in managing public services. Keywords: innovation, public service, public service mall, Rogers’ innovation attributes